2020
DOI: 10.18502/kss.v4i7.6850
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Technology Affect Income Inequality in Indonesia?

Abstract: Economic growth is insufficient to be a sole indicator of the population's welfare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Moreover, the results also show that high technology exports have a negative impact on income inequality. These results are in line with the findings of Saraswati, Maski, Kalug, and Sakti (2020), who revealed that sometimes a small group of people contains a larger portion of the national wealth because of the enhanced earnings opportunities through the use of high-quality resources, which they can afford on account of their economic power. However, the facility to export high technology at an affordable price removes inequality in income distribution because it gives equal chances to grow economically at all levels.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the results also show that high technology exports have a negative impact on income inequality. These results are in line with the findings of Saraswati, Maski, Kalug, and Sakti (2020), who revealed that sometimes a small group of people contains a larger portion of the national wealth because of the enhanced earnings opportunities through the use of high-quality resources, which they can afford on account of their economic power. However, the facility to export high technology at an affordable price removes inequality in income distribution because it gives equal chances to grow economically at all levels.…”
Section: Discussionsupporting
confidence: 92%
“…Our study results demonstrate that the FinTech variable, which is proxied by the usage of mobile phones to pay and receive money (age +15) in the past year, has a positive and significant impact on income inequalities in both the GINI coefficient and the Palma ratio proxies at the 1% and 10% significance levels. Thus, the findings of our study are robust in both proxies of income inequalities and support those of Saraswati et al (2020), who find that FinTech provides more benefit to the rich in Indonesia than the poor and broadens the income inequalities gap. The results are not consistent with the findings of Asongu and Nwachukwu (2018), Asongu and Odhiambo (2019), X.…”
Section: Pooled Ols Regression Analysissupporting
confidence: 85%
“…Moreover, Hodula (2023) investigates the impact of FinTech and big tech credit on income inequalities in a panel data set of 78 countries from 2013-2019 and concludes that FinTech and other big tech developments are linked with a reduction in income inequality. In contrast, Saraswati et al (2020) show that FinTech development increases income inequality in Indonesia using the partial adjustment model from 1990-2017. This may be due to the fact that FinTech by itself requires prerequisite initial investments for its utilization, such as knowledge, smart phones, ICT infrastructure, electricity, and capital.…”
Section: Fintech and Income Inequalitymentioning
confidence: 90%
“…Based on the 2019 technological readiness index data by UNCTAD, out of 15 middle-income countries there are seven countries that have an index value of <0.5 which means that they are less prepared to fully utilize fintech in their financial sector. Research findings by [12] show that the development of fintech 3.0 has a positive short-term effect on income inequality in Indonesia. These findings indicate that the development of fintech 3.0 which began in 2000 increased income inequality in Indonesia.…”
Section: Discussionmentioning
confidence: 99%